French suite a book of essays - Fried, Michael 1939- (Reaktion Books, 2022)
French Suite examines a range of important French painters and two writers, Baudelaire and Flaubert, from the brothers Le Nain in the mid-seventeenth century to Manet, Degas, Corot, Daubigny and the Impressionists in the later nineteenth century. A principal theme of the essays is a fundamental concern of Fried’s throughout his career: the relation between painting and beholder. Fried’s typically vivid and strongly argued essays offer many new readings and unexpected insights, transforming our understanding of both familiar and lesser-known French artistic and literary works
Keywords: Geschichte 1800-1900; Malerei; Frankreich; Aufsatzsammlung